Analysis of small molecule antibody–drug conjugate catabolites in rat liver and tumor tissue by liquid extraction surface analysis micro‐capillary liquid chromatography/tandem mass spectrometry. (29th February 2016) - Lanshoeft, Christian; Stutz, Gerhard; Elbast, Walid; Wolf, Thierry; Walles, Markus; Stoeckli, Markus; Picard, Franck; Kretz, Olivier
Abstract : Rationale: Antibody–drug conjugates (ADCs) are some of the most promising antibody‐related therapeutics. The fate of the cytotoxic moiety of ADCs in vivo after proteolytic degradation of the antibody needs to be well understood in order to mitigate toxicity risks and design proper first in patient studies. Methods: The feasibility of liquid extraction surface analysis micro‐capillary liquid chromatography/tandem mass spectrometry (LESA‐μLC/MS/MS) was tested for direct surface sampling of two possible ADC catabolites composed of synthetically modified maytansinoid (DM1) and 4‐[ N ‐maleimidomethyl]cyclohexane‐1‐carbonyl (MCC) from rat liver and tumor tissue. Moreover, the iMatrixSpray was incorporated to prepare calibration standards (Cs) and quality control (QC) samples by spraying analyte solution at different concentrations directly on blank tissue. Results: Lys‐MCC‐DM1 sprayed on blank liver tissue was homogeneously distributed (12.3% variability). The assay was selective (inference ≤20%) and linear from 50.0 to 1000 ng/mL without any carry‐over. Inter‐run accuracy and precision were ≤2.3% and ≤25.9% meeting acceptance. Lys‐MCC‐DM1 was the only catabolite detected in liver and tumor tissue and was most likely responsible for the total radioactivity signal in liver tissue 72 h post‐dose measured by quantitative whole body autoradiography (QWBA). Conclusions: Both analytical assays (LESA‐μLC/MS/MS and QWBA) are complementary to each other and provide useful quantitative and qualitative information in spatial tissue distribution of ADCs and their related catabolites. Copyright © 2016 John Wiley & Sons, Ltd.